Current Understanding of Structure–Processing–Property Relationships in BaTiO3–Bi(M)O3 Dielectrics. Issue 9 (1st September 2016) - Beuerlein, Michaela A.; Kumar, Nitish; Usher, Tedi‐Marie; Brown‐Shaklee, Harlan James; Raengthon, Natthaphon; Reaney, Ian M.; Cann, David P.; Jones, Jacob L.; Brennecka, Geoff L.
Abstract : As part of a continued push for high permittivity dielectrics suitable for use at elevated operating temperatures and/or large electric fields, modifications of BaTiO3 with Bi( M )O3, where M represents a net‐trivalent B ‐site occupied by one or more species, have received a great deal of recent attention. Materials in this composition family exhibit weakly coupled relaxor behavior that is not only remarkably stable at high temperatures and under large electric fields, but is also quite similar across various identities of M . Moderate levels of Bi content (as much as 50 mol%) appear to be crucial to the stability of the dielectric response. In addition, the presence of significant Bi reduces the processing temperatures required for densification and increases the required oxygen content in processing atmospheres relative to traditional X7R‐type BaTiO3 ‐based dielectrics. Although detailed understanding of the structure–processing–property relationships in this class of materials is still in its infancy, this article reviews the current state of understanding of the mechanisms underlying the high and stable values of both relative permittivity and resistivity that are characteristic of BaTiO3 ‐Bi( M )O3 dielectrics as well as the processing challenges and opportunities associated with these materials.